Dystrybucja produktów ubezpieczeniowych przez organizacje sieciowe - Obstawski, Zdzisław (Network Distribution of Insurance Products, 2005)
The article presents the principles of forming modern networks of insurance products distribution, including relating current legal possibilities. Moreover, the most important elements in the development of distribution strategies were shown. The analysis of the presented facts lead the author to the conclusion that advantages of network distribution of insurance may make some insurance companies completely change traditional distribution strategies of their products. According to the author, some insurers should consider the possibility to use network distribution companies completing their channels of insurance coverage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 363-371